Restoration of Traditional Children's Play in Iranian Nomadic Societies (Case Study of Kohgilouyeh and Boyer Ahmad) - Laleh Taheri; Golshan Chahian (MDPI AG, 2015)
This article aims to provide an insight into play as an important aspect of children's lives in an under-studied area of Iran. Our observations focus on the province of Kohgilouyeh and Boyer Ahmad with its ancient nomadic cultures. Through first-hand knowledge and lived experiences, supplemented by available literature, we seek to look at children's games in the frame of culture change, exploring their relationship with children's health and wellbeing. Play, as in every region in the world, conveys and reflects the dominant culture and teaches the values of the society in which the children live in the here and now and in which they will have to function as adults. Yet, types of play are not static. They develop alongside social, political and economic changes and embrace new forms emerging from modern lifestyles. The latter sometimes come into conflict with and challenge the local culture and traditional types of play, which are based on the lives and histories of the indigenous peoples and local communities. A sample of traditional tribal forms of play is analyzed for their health, entertainment and fun aspects. Such play allows children to prepare for life's realities, in particular for a life of cooperation. By contrast, whilst also providing children with tools and skills for the needs of modern life, new types of play focus more on competition and individualism. This divergence expressed in different types of play widens the generation gap and contributes to alienation. The shift from a collective to individualistic lifestyle thus has an unsettling impact on the community and impacts on the emotional and physical wellbeing of children. We will describe types of play and their role in the holistic development of nomadic children, as well as the impact of modernization and social change, including sedentarization. The article will highlight some consequences of the demise of indigenous play, through observation and analytical comparison of children's play in three generations. Based on the insights gained, the authors offer recommendations on how to restore traditional play and games through redesigning them to be capable of adaptation to changes in lifestyles.